The impact of presenting problem based guidelines for children with medical problems in an accident and emergency department. Issue 2 (21st January 2004) - Armon, K; MacFaul, R; Hemingway, P; Werneke, U; Stephenson, T
Abstract : Aims: To evaluate the impact of presenting problem based guidelines in managing children with either diarrhoea (with or without vomiting) or seizure (with or without fever). Methods: This prospective observational study with an intervention was based on a paediatric accident and emergency (A&E) department in Nottingham. All patients (either GP or self referred) were acute attenders aged 0–15 years, with a medical presenting problem during 4 months in the spring of 1997 and 1999. Five hundred and thirty-one diarrhoea attendances (292 before guideline implementation and 239 after) and 411 seizure attendances (212 before guideline implementation and 199 after) were recorded. Evidence based and consensus ratified guidelines developed for the study were implemented using care pathway documentation. Process (documentation, time in the department, investigations, treatment) and outcome (admission to hospital, returns to A&E) data were collected from case notes. Results: The percentage of children investigated with blood tests fell significantly (haematology requests in diarrhoea presentations from 11% to 4%, biochemistry in seizure presentations from 29% to 17%). Intravenous infusions in diarrhoea presenters fell (9% to 1%), and more appropriate oral fluids were used. Management time in A&E was reduced (diarrhoea presenters: median of 55–40 minutes, seizure presenters: 80–55 minutes, but remained static for other presenting problems). Marked improvements in documentation were seen. Admission rates for diarrhoea attenders increased (27% to 34%) but remained the same for seizure (69% v 73%) Conclusions: The implementation of a presenting problem based guideline as a care pathway was associated with improvements in the quality of care by: improved documentation; reduced invasive investigations; more appropriate treatment, and reduced time spent in A&E.